2017
DOI: 10.1186/s40164-017-0078-1
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose methotrexate in sickle-cell disease: a pilot study with rationale borrowed from rheumatoid arthritis

Abstract: BackgroundInflammation is a major feature of sickle cell disease (SCD). Low-dose methotrexate (MTX) has long been used in chronic inflammatory diseases. This pilot study examined the MTX effect on acute vaso-occlusive pain crises (VOC) in SCD patients.MethodsFourteen adults on hydroxyurea with severe and refractory VOC received one intramuscular injection of 10 mg of MTX per week for 12 weeks. A single weekly dose of 5 mg of leucovorin was administered orally 48 h after each MTX injection. The primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…A small study of 14 adults on HU with severe and refractory SCD trialled the use of methotrexate by injection 10 mg weekly for 12 weeks. The study demonstrated an improvement in chronic pain and quality of life 38 . As mentioned previously, methotrexate's main drawback is cytopenia which must duly be gauged in patients who are already on HU.…”
Section: Therapy Of Autoimmune Disease In Sickle Cell Diseasesupporting
confidence: 52%
See 1 more Smart Citation
“…A small study of 14 adults on HU with severe and refractory SCD trialled the use of methotrexate by injection 10 mg weekly for 12 weeks. The study demonstrated an improvement in chronic pain and quality of life 38 . As mentioned previously, methotrexate's main drawback is cytopenia which must duly be gauged in patients who are already on HU.…”
Section: Therapy Of Autoimmune Disease In Sickle Cell Diseasesupporting
confidence: 52%
“…The study demonstrated an improvement in chronic pain and quality of life. 38 As mentioned previously, methotrexate's main drawback is cytopenia which must duly be gauged in patients who are already on HU. Its safe usage in patients of a childbearing age must also be considered.…”
Section: Th Er a Py Of Au Toi M Mu N E Dise Ase I N Sick L E Ce L L D...mentioning
confidence: 99%
“…The authors observed that the frequency of VOC did not decrease; however, avascular necrosis pain diminished, bringing gain in physical functioning, which suggested some benefit with the combination of MTX and hydroxyurea. Low platelet counts were observed as adverse effects with the double therapy [ 72 ]. Furthermore, patients with SCD will have compensatory reticulocytosis which can be impaired with MTX.…”
Section: Methodsmentioning
confidence: 99%
“…An improvement in the anemia was observed. According to Brandalize, the use of methotrexate resulted in an improvement in pain and joint functionality; however, a disturbance in the platelet count was observed [14].…”
Section: Case Presentationmentioning
confidence: 99%